Suivi de la Fréquence Cardiaque et de la Pression Artérielle des Judokas Obèses et en Surpoids Âgés de 10-12 ans, Pendant le Confinement COVID-19 - Bounab, Chaker; Kheiri, Samir (جامعة العربي بن مهيدي أم البواقي - معهد علوم وتقنيات الشاطات البدنية والرياضية, 2022)
The objective of this work is to highlight and then compare the resting heart rate (HR), the systolic (SAP) and diastolic (PAD) blood pressure of obese and overweight children, before and after the confinement of covid-19. To do this, we used the descriptive methodology, by applying the pre and post-test on a group of 16 children whose characteristics: BMI= 25.796 ± 4.471 kg/m², age = 10.792 ± 0.495 years, have a experience of 3± 2,066 years. Trained at the level of judo clubs, twice a week at the rate of an hour and a half per session, plus the session of physical education and sports at school. The analysis of the results obtained showed: a statistically significant difference for the parameters: Fc, and PAS (p<0.05), and a statistically insignificant difference for PAD.
Keywords: فيروس كورونا "كوفيد-19" -- مرض السمنة المفرطة -- التربية الرياضية